2021
DOI: 10.3390/ijerph18105428
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Demographic Correlates of Substance Use among Adults with Mental Illness in Eastern Cape, South Africa: A Cross-Sectional Study

Abstract: This study reports on the prevalence and demographic correlates of substance use among individuals with mental illness in the Eastern Cape, South Africa. This cross-sectional study was conducted in the Outpatient Clinic of a large hospital in the Eastern Cape, South Africa. A pre-validated tool on alcohol and psychoactive drug use was administered to 390 individuals with mental illness. Multivariable logistic regression models were fitted to explore the demographic correlates of alcohol and psychoactive drug u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 49 publications
3
18
0
1
Order By: Relevance
“…From our findings, mental and behavioral disorders due to psychoactive substance use (F10-F19) were more common in male patients than in female patients ( P < 0.0001), consistent with their increased exposure to alcohol, drug, and other psychoactive substances ( 35 , 36 ), whereas mood [affective] disorders were significantly more frequent in female than in male patients ( P = 0.048), which is related to the higher incidence of depression in women ( 4 ). Correspondingly, there were sex differences in the prescriptions of antidepressant drugs (51.9% males vs. 45.4% females) and anti-anxiety drugs (male 36.9% vs. female 47%) ( 37 ), and depression accompanied by anxiety disorders or anxiety symptoms was more common in female patients ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 81%
“…From our findings, mental and behavioral disorders due to psychoactive substance use (F10-F19) were more common in male patients than in female patients ( P < 0.0001), consistent with their increased exposure to alcohol, drug, and other psychoactive substances ( 35 , 36 ), whereas mood [affective] disorders were significantly more frequent in female than in male patients ( P = 0.048), which is related to the higher incidence of depression in women ( 4 ). Correspondingly, there were sex differences in the prescriptions of antidepressant drugs (51.9% males vs. 45.4% females) and anti-anxiety drugs (male 36.9% vs. female 47%) ( 37 ), and depression accompanied by anxiety disorders or anxiety symptoms was more common in female patients ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 81%
“…Studies have shown that young, unemployed men living in rural areas are factors strongly associated with substance use. 29 Similarly, the current study has shown that substance use was prevalent among young male patients and, given the readmissions, is likely an ongoing challenge in communities.…”
Section: Number Of Readmissionsmentioning
confidence: 60%
“…Substance use causes a significant burden on individual productivity, the economy and the social aspects of individuals, as well as families and communities. 29 Approximately 13.3% of South Africans were found to have used drugs in their lifetime. 30 The role of environment cannot be discounted in the case of substance use, including the level of urbanisation and socio-economic status.…”
Section: Number Of Readmissionsmentioning
confidence: 99%
“…It is well understood that mental health issues lead to drug use (UNODC 2015). Several studies have found a higher prevalence of SUDs in people with mental illnesses (range of 21.3% -55.6%) than in the general population (3% -4%) (Tindimwebwa, Ajayi & Adeniyi 2021).…”
Section: Introductionmentioning
confidence: 98%
“…It is well understood that mental health issues lead to drug use (UNODC 2015 ). Several studies have found a higher prevalence of SUDs in people with mental illnesses (range of 21.3% – 55.6%) than in the general population (3% – 4%) (Tindimwebwa, Ajayi & Adeniyi 2021 ). Women are more likely than men to attribute their substance use to trauma or stressors such as relationship issues, environmental stress or family issues (UNODC 2018 ).…”
Section: Introductionmentioning
confidence: 99%